Additional Treatments in The Packaging Process Increase Sales Value and Profit Margin of Bell Pepper (Capsicum annum var. Grossum) in Traditional Market - Dewi, Ni Kadek Sri Mariana; Apriadi, I Gst. Ngr.; Sucipta, I Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Paprika is one type of vegetable horticulture plant. Based on the results of the preliminary study conducted, the price per kg of paprika in the traditional market is Rp25,000, while for the modern market the price per kg of paprika is Rp65,190. The price of paprika in the modern market is higher than the price in the traditional market because of the additional treatment given. This study aims to determine the additional treatment given to paprika in traditional markets and to determine the profit marginof handling paprika in traditional markets. This research uses descriptive quantitative research methods. This research was conducted in one of the traditional markets of Candikuning, Tabanan Regency and the modern market of Tiara Dewata Denpasar. The results showed that the traditional market did not give additional treatment to the peppers before being sold, in contrast to the modern market Tiara Dewata which gave additional treatment before the pepper was sold. Additional treatment is to package chili using plastic wrap. The results of this study also show the profit margins of the two markets, namely the profit margin obtained by the traditional market of 2.93% while the profit margin of the modern market is 27%. From the assumption of traditional market profit margin calculation, only the addition of paprika packaging with plastic wrap gives an increase in the profit margin of 18.35%.